BindingDB Entry 50038290: Ohioensins F and G: protein tyrosine phosphatase 1B inhibitory benzonaphthoxanthenones from the Antarctic moss Polytrichastrum alpinum. - BindingDB (BindingDB, 2012)
Small molecule binding data for protein Protein-tyrosine phosphatase 1B, Uniprot P18031